Coagulation factor VIII: Relationship to cardiovascular disease risk and whole genome sequence and epigenome‐wide analysis in African Americans. (20th February 2020) - Raffield, Laura M.; Lu, Ake T.; Szeto, Mindy D.; Little, Amarise; Grinde, Kelsey E.; Shaw, Jessica; Auer, Paul L.; Cushman, Mary; Horvath, Steve; Irvin, Marguerite R.; Lange, Ethan M.; Lange, Leslie A.; et al.
Abstract: Background: Prospective studies have suggested higher factor VIII (FVIII) levels are an independent risk factor for coronary heart disease (CHD) and stroke. However, limited information, including on genetic and epigenetic contributors to FVIII variation, is available specifically among African Americans (AAs), who have higher FVIII levels than Europeans. Objectives: We measured FVIII levels in ~3400 AAs from the community‐based Jackson Heart Study and assessed genetic, epigenetic, and epidemiological correlates of FVIII, as well as incident cardiovascular disease (CVD) associations. Methods: We assessed cross‐sectional associations of FVIII with CVD risk factors as well as incident CHD, stroke, heart failure, and mortality associations. We additionally assessed associations with TOPMed whole genome sequencing data and an epigenome‐wide methylation array. Results: Our results confirmed associations between FVIII and risk of incident CHD events and total mortality in AAs; mortality associations were largely independent of traditional risk factors. We also demonstrate an association of FVIII with incident heart failure, independent of B‐type natriuretic peptide. Two genomic regions were strongly associated with FVIII ( ABO and VWF ). The index variant at VWF is specific to individuals of African descent and is distinct from the previously reported European VWF association signal. Epigenome‐wide association analysis showed significant FVIII associations with several CpG sites in the ABO region. However, after adjusting for ABO genetic variants, ABO CpG sites were not significant. Conclusions: Larger sample sizes of AAs will be required to discover additional genetic and epigenetic contributors to FVIII phenotypic variation, which may have consequences for CVD health disparities.